2021
DOI: 10.1007/s12328-021-01424-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the outcomes of gastrointestinal surgery

Abstract: COVID-19 pandemic has brought a paradigm shift in the treatment of various surgical gastrointestinal disorders. Given the increasing number of patients requiring hospitalization and intensive care for SARS-CoV-2 infections, various surgical departments worldwide were forced to stop or postpone elective surgeries to save the health resources for COVID-19 patients. Since the declaration of the COVID-19 pandemic by the World Health Organization on 12th March 2020, the recommendations from the surgical societies k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
(85 reference statements)
0
14
0
4
Order By: Relevance
“…The COVID-19 pandemic had a pronounced impact on abdominal surgery including tumor and transplant surgery [ 2 ]. Whether laparoscopic cholecystectomy for acute cholecystitis should be performed or not during the pandemic was heavily debated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic had a pronounced impact on abdominal surgery including tumor and transplant surgery [ 2 ]. Whether laparoscopic cholecystectomy for acute cholecystitis should be performed or not during the pandemic was heavily debated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous elective surgeries have been postponed to create treatment capacity for COVID-19 patients. In several centers, elective gastrointestinal and bariatric operations, elective endoscopies and liver transplants have been cancelled [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent global survey ( 11 ) showed that hip fracture service was disrupted during the pandemic, thereby impacting health and social care experienced by the patients. This dilemma was also noted in cardiovascular ( 12 ), gastrointestinal, and ( 13 ) oncology ( 14 ) surgeries.…”
Section: Introductionmentioning
confidence: 92%
“…A nivel quirúrgico, muchos estudios han evidenciado una reducción en el número de procedimientos urgentes realizados durante la pandemia (6)(7)(8)(9) , junto a este hecho también se ha observado en algunos estudios un aumento del tiempo de evolución hasta recibir tratamiento debido al retraso diagnóstico y un aumento de la morbimortalidad (9) .…”
Section: Discusión Y Conclusionesunclassified